EFFECTIVE METHOD OF THE SURGICAL TREATMENT OF THE CHRONIC SUPPURATIVE-FISTULOUS FORM OF THE EPITHELIAL COCCYGEAL PASSAGE AT THE ABSCESS STAGE - Владимир Павлович Ревицкий; Вера Ивановна Латынина; Татьяна Константиновна Ядыкина; Сергей Николаевич Филимонов (Медицина в Кузбассе)
Objective – the elaboration of an effective original method for the surgical treatment of the chronic suppurative-fistulous form of the epithelial coccygeal passage at the abscess stage without a damage of the intergluteal fold.